2012
DOI: 10.4415/ann_12_03_13
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of vitamin D for prevention and treatment of tuberculosis and infectious diseases

Abstract: Abstract.Introduction.Vitamin D deficiency (VDD) is a common condition among several populations in the world. VDD is associated with higher incidence of immune system disorders and faster progression of some infectious diseases. Vitamin D is known to be of physiological importance, it is considered an essential micronutrient for the bone health and plays a beneficial role in the prevention and/or treatment of a number of chronic diseases. Vitamin D has a complex action on the immune system. Results. Evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 85 publications
0
31
0
3
Order By: Relevance
“…In recent years, vitamin D deficiency in humans has received significant attention [7], [51], [52]. It has been shown to play a potent role in the susceptibility to respiratory infectious diseases [53], [54]. A still unresolved question arising from ongoing laboratory and clinical research is the serum vitamin D concentrations needed to elicit an optimal immune response [55].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, vitamin D deficiency in humans has received significant attention [7], [51], [52]. It has been shown to play a potent role in the susceptibility to respiratory infectious diseases [53], [54]. A still unresolved question arising from ongoing laboratory and clinical research is the serum vitamin D concentrations needed to elicit an optimal immune response [55].…”
Section: Discussionmentioning
confidence: 99%
“…Calcitriol activation of VDRs induces cathelicidin antimicrobial peptide (CAMP) gene expression and subsequently production of cathelicidin [11]. This important antimicrobial peptide, cathelicidin, disrupts the bacterial cell membrane [12] and induces autophagy in monocytes, creating an antimicrobial effect (FIGURE 1) [13][14][15]. Of note, this vitamin D-directed antimicrobial action does not occur in the absence of cathelicidin; instead, enhanced intracellular mycobacterial growth takes place [16].…”
mentioning
confidence: 91%
“…Vitamins have been found to regulate immunity, and a number of studies have reported the effect of vitamins as adjunct to treat tuberculosis (Parida et al, 2015;He et al, 2018). For example, vitamins A, C and D have been used as adjunct to complement anti-tuberculosis drugs (Dini and Bianchi, 2012;Vilcheze et al, 2013;Syal et al, 2015). The active form of thiamin (Vitamin B1, V B1 ), thiamin diphosphate (ThDP) (Begley et al, 1999;Settembre et al, 2003;Pohl et al, 2004), is an essential cofactor in all organisms, taking an important role in energy metabolism and degradation of sugars.…”
Section: Introductionmentioning
confidence: 99%